Determinants of vitamin D status of healthy office workers in Sydney, Australia. Issue 189 (May 2019) - Fayet-Moore, Flavia; Brock, Kaye E.; Wright, Jutta; Ridges, Leisa; Small, Penelope; Seibel, Markus J.; Conigrave, Arthur D.; Mason, Rebecca S.
Highlights: We examined determinants of vitamin D status of healthy office workers in Sydney. These were sun exposure, phototype, body part exposed and fish consumption. Blood 25OHD (vitamin D) was measured at the end of summer and the end of winter. Vitamin D status at end-winter was correlated with vitamin D status at end-summer. Fish intake was important to maintenance of adequate vitamin D status in winter. Abstract: Low vitamin D status, measured as 25-hydroxyvitamin D (25OHD), has been linked to increased risk of osteoporosis and other disorders. Due to the indoor nature of office work, there may be an increased risk of 25OHD deficiency in this group. The aim of the current study was to evaluate seasonal variations of 25OHD in a population of healthy office workers, and to assess the effect of sun exposure behaviour, skin pigmentation, physical activity (PA) and dietary intake on serum 25OHD concentrations. We assessed the vitamin D status of healthy office workers in Sydney, Australia, at the end of summer (n = 103) and then at the end of winter (n = 71). Data on anthropometry, PA, dietary intake, sun exposure and skin phototype were collected along with blood samples. Serum 25OHD was measured by radioimmunoassay. Mean 25OHD concentration in late summer was 68 ± 27 nmol/L (range: 24–160 nmol/L), and in late winter was 59 ± 32 nmol/L (range: 15–174 nmol/L). 25OHD deficiency (<50 nmol/L) was observed in 29% and 42% of participants at end-summer and end-winter, respectively. Almost 10% of individuals were extremely deficient (<25 nmol/L) at end-winter, particularly those with dark skin (phototypes 5 and 6). Independent predictors of end-summer 25OHD were skin phototype (p < 0.02), summer sun exposure (p < 0.001) and skin area exposed (p = 0.005). The strongest predictor of end-winter 25OHD was end-summer 25OHD concentration (p < 0.001). If this was excluded from the model, the independent predictors of end-winter 25OHD were skin phototype (p < 0.01), sun exposure in winter (p = 0.01) and oily fish consumption (p < 0.05). Sunscreen use was significantly associated with higher vitamin D status (p < 0.05) as those who used sunscreen were also more likely to spend time outdoors. We conclude that sun exposure is beneficial for vitamin D status even with sunscreen use. Vitamin D supplements should be targeted to individuals who are darker skinned or unable to obtain adequate sun exposure, particularly during the winter months.